Methylation of promoters of microRNAs and their host genes in myelodysplastic syndromes. Issue 12 (December 2013) - Erdogan, Begum; Bosompem, Amma; Peng, Dunfa; Han, Leng; Smith, Emily; Kennedy, Mija E.; Alford, Catherine E.; Wu, Huiyun; Zhao, Zhongming; Mosse, Claudio A.; El-Rifai, Wael; Kim, Annette S.
Abstract Myelodysplastic syndromes (MDS) are a group of hematopoietic malignancies characterized by ineffective hematopoiesis. Recently, we identified MDS-associated microRNAs (miRNAs) that are down-regulated in MDS. This study examines possible explanations for that observed down-regulation of miRNA expression in MDS. Since genomic losses are insufficient to explain the down-regulation of all our MDS-associated miRNAs, we explored other avenues. We demonstrate that these miRNAs are predominantly intragenic, and that, in many cases, they and their host genes are expressed in a similar pattern during myeloid maturation, suggesting their co-regulation. This co-regulation is further supported by the down-regulation of several of the host genes in MDS and increased methylation of the shared promoters of several miRNAs and their respective host genes. These studies identify a role of hypermethylation of miRNA promoters in the down-regulation of MDS-associated miRNAs, unifying research on miRNAs in MDS and epigenetic regulation in MDS into a common pathway.